EEG patterns and their correlations with short- and long-term mortality in patients with hypoxic encephalopathy. Issue 11 (November 2021) - Willems, Laurent M.; Trienekens, Franziska; Knake, Susanne; Beuchat, Isabelle; Rosenow, Felix; Schieffer, Bernhard; Karatolios, Konstantinos; Strzelczyk, Adam
Highlights: Early EEG is a reliable biomarker for overall, short- and long-term prognosis in patients with hypoxic encephalopathy. Prevalence of EEG suppression is associated with a poor short-term prognosis. Different EEG pattern are associated with an increased overall, short- and long-term mortality to various extents. Abstract: Objective: To analyze the association between electroencephalographic (EEG) patterns and overall, short- and long-term mortality in patients with hypoxic encephalopathy (HE). Methods: Retrospective, mono-center analysis of 199 patients using univariate log-rank tests (LR) and multivariate cox regression (MCR). Results: Short-term mortality, defined as death within 30-days post-discharge was 54.8%. Long-term mortality rates were 69.8%, 71.9%, and 72.9%, at 12-, 24-, and 36-months post-HE, respectively. LR revealed a significant association between EEG suppression (SUP) and short-term mortality, and identified low voltage EEG (LV), burst suppression (BSP), periodic discharges (PD) and post-hypoxic status epilepticus (PSE) as well as missing (aBA) or non-reactive background activity (nrBA) as predictors for overall, short- and long-term mortality. MCR indicated SUP, LV, BSP, PD, aBA and nrBA as significantly associated with overall and short-term mortality to varying extents. LV and BSP were significant predictors for long-term mortality in short-term survivors. Rhythmic delta activity, stimulus induced rhythmic, periodic or ictal discharges and sharp waves were not significantly associated with a higher mortality. Conclusion: The presence of several specific EEG patterns can help to predict overall, short- and long-term mortality in HE patients. Significance: The present findings may help to improve the challenging prognosis estimation in HE patients.